Investigation of a circular TE11-TE01-mode converter in stepped waveguide technique. Issue 3 (10th April 2015) - Schulz, Christian; Baer, Christoph; Musch, Thomas; Rolfes, Ilona; Will, Bianca
Abstract : A compact and broadband TE11 -TE01 -mode converter, suitable for various industrial applications like bypass level measurements, is presented in this contribution. Based on stepped waveguide technique, the main advantages of the recommended converter design and the specific field distribution of the TE01 -mode are discussed in detail. The converter is presented exemplary for a frequency range from 23 to 28 GHz, which corresponds to a bandwidth of approximately 20 % of the center frequency. Numerous three-dimensional electromagnetic field simulations are performed to optimize the converter and to investigate its reflection and transmission behavior. Realized by six different single elements and 11 parts in total, fast and effective simulations can be performed with CST Microwave Studio. Considering realistic production process parameters, like fillets or tolerances, a good return loss better 17 dB, an insertion loss of 0.1 dB, and an excellent mode purity are achieved. Compared with back-to-back, realistic disturber scenario, and far-field measurements with a first prototype, the expected excellent converter behavior can be validated without limitations. Hence, the suitability of the presented converter design is proven and the feasibility is demonstrated.